2003
DOI: 10.1002/chem.200304963
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Conformation and Interplay of p‐Sulfonatocalix[6]arene as Lanthanide Crown Ether Complexes

Abstract: Control over the conformational flexibility of p-sulfonatocalix[6]arene in the solid state is possible in the presence of varied stoichiometric amounts of [18]crown-6 and selected lanthanide(III) chlorides. Complexes 1 and 2 have the calixarene in the elusive up-up double cone conformation, whilst complex 3 has the calixarene in the centrosymmetric up-down double partial cone conformation, whereby it acts as a divergent receptor. Complex 1 has a double molecular capsule arrangement which is composed of two p-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 76 publications
7
68
0
1
Order By: Relevance
“…It is suggested that the pseudo 'thiacalix [3]arene-like' cavities, like a small macrocyclic ring assembled each of three p-sulfonatophenol units, assemble through a combination of hydrogen bonding and hydrophobic interactions in aqueous media. In previous reports, 'up-up' double conical and 'up-down' double conical conformations possessing pseudocavities were observed [17]. Likewise, complex I adopts a similar 'up-down' double partial-cone conformations as those reported for metal complexes of p-sulfonatothia-and calix [6]arenes [15][16][17][47][48][49].…”
Section: X-ray Crystallographysupporting
confidence: 62%
See 3 more Smart Citations
“…It is suggested that the pseudo 'thiacalix [3]arene-like' cavities, like a small macrocyclic ring assembled each of three p-sulfonatophenol units, assemble through a combination of hydrogen bonding and hydrophobic interactions in aqueous media. In previous reports, 'up-up' double conical and 'up-down' double conical conformations possessing pseudocavities were observed [17]. Likewise, complex I adopts a similar 'up-down' double partial-cone conformations as those reported for metal complexes of p-sulfonatothia-and calix [6]arenes [15][16][17][47][48][49].…”
Section: X-ray Crystallographysupporting
confidence: 62%
“…The inclusion of organic and/or inorganic compounds into their flexible cavities and the coordination of organic/metal ions in supramolecular chemistry have been reported [7][8][9]. In particular, water-soluble p-sulfonatocalix [n]arenes (n = 4−8) have attracted significant attention owing to several intriguing properties in both the solution and solid states [10][11][12][13][14][15][16][17][18][19][20][21]. Their functional and conformational characteristics lead to a macrocyclic biological mimic for interesting assembled architectures [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Guest-induced conformational distortion can afford a bismolecular capsule arrangement, 18 and similar bis-capsules can be formed for SO 3 [6] and SO 3 [8] with 18-crown-6 and tetraphenylphosphonium guest species respectively, as parts of lanthanide metal complexes. 15,19 Considering the substantial number of complicated multicomponent supramolecular solid-state complexes reported for SO 3 [4] and the larger analogues, relatively few simple metal complexes of the SO 3 [4] (other than alkali metals and some formed in the absence of guest) have been reported. [20][21][22][23] Herein we report the formation of three metal complexes either with incorporation or exclusion of the metal salt anion.…”
Section: Introductionmentioning
confidence: 99%